Severe Interstitial Lung Disease and Manic Symptoms Secondary to Corticosteroids in a Patient with Systemic Lupus Erythematosus and Secondary Sjögren’s Syndrome - Serra, Sofia Silvério (2017)
Interstitial lung disease occurs in up to 25% of patients with Sjögren’s syndrome and 2% - 8 % of patients with systemic lupus erythematosus. Corticosteroid therapy remains the main treatment for systemic lupus erythematosus. However, it can be associated with several neuropsychiatric disorders especially with prednisolone at a dose of more than 40 mg/day. We present the case of a 51-year-old patient with systemic lupus erythematosus and secondary Sjögren’s syndrome with severe pulmonary involvement four years after the diagnosis. Chest computed tomography revealed neofibrosis and ground glass appearance pattern. After increasing the dose of prednisolone to 60 mg/day, the patient presented a manic episode. There was need of hospitalization and the situation was considered to be secondary to corticosteroids at high doses. Central neurological involvement by organic disease was excluded.We introduced monthly perfusion of cyclophosphamide for six months and later started mycophenolate mofetil 2 g/day, reducing prednisolone to 10 mg/day and maintaining hydroxychloroquine 400 mg/day, with control of disease activity.